Genome Wide Association mapping of grain and straw biomass traits in the rice Bengal and Assam Aus Panel (BAAP) grown under alternate wetting and drying and permanently flooded irrigation - Norton, Gareth J.; Travis, Anthony J.; Douglas, Alex; Fairley, Susan; Alves, Eduardo De Paiva; Ruang-areerate, Panthita; Naredo, Ma. Elizabeth B.; McNally, Kenneth L.; Hossain, Mahmud; Islam, Md. Rafiqul; Price, Adam H. (Frontiers Media, 2018)
Growing demand for staple crops like rice will need to be achieved predominately through agricultural intensification and more efficient use of inputs. To meet this demand it is essential that the genetic diversity within rice is fully utilised. The aus subpopulation is considered an underappreciated resource within that diversity. A new rice panel, the Bengal and Assam Aus Panel (BAAP) of 266 aus accessions was generated with~2 million informative SNPs obtained using skim sequencing at ~4x depth. The BAAP was grown in the field in Bangladesh in the ‘boro’ season under both continuously flooded and Alternate Wetting and Drying (AWD) irrigation during 2013 and 2014 in Mymensingh and during 2014 in Madhupur. Heading date, grain mass, straw biomass and harvest index were measured. The majority (94%) of BAAP accessions flowered within a relatively small window of 10 days. The AWD irrigation treatment generally caused an increase in grain mass, but no significant genotype by treatment interactions were detected for this trait. Shoot biomass was the only trait that showed evidence of genotype by treatment interaction. The average LD (Linkage Disequilibrium) decay across the genome was 243 Kbp. Genome wide association mapping revealed 115 quantitative trait loci (QTLs). There was little evidence of QTLs specific to the irrigation treatment, and only a few QTLs co-localised with known genes. However, some QTLs were detected across multiple sites and years. These QTLs should be targets for breeding, and include a region around 2.2 Mbp on chromosome 1, a large region in the middle of chromosome 7 and two regions on chromosome 11 (~10 Mbp and ~29 Mbp). The BAAP appears to be a valuable addition to the growing collection of GWA mapping populations of rice.